Seed treatment, stress tolerance, and genetic variability of Moringa oleifera LAM - Soares, Tássia Fernanda Santos Neri (2023)
The tress species Moringa oleifera Lam. is popularly known for its multiple-purpose applications. In view of the high nutritional value of the leaves, moringa can be used for animal as well human food. The species is native to India and widespread in tropical and subtropical regions around the world. The purpose of this study was to: (1) discuss the importance of the moringa leaf extract and assess its efficiency in moringa seed treatment; (2) evaluate the tolerance of the species to low temperatures stress; and (3) estimate the genetic diversity of the Active Moringa Germplasm Bank of Embrapa Tabuleiros Costeiros. To this end, the moringa leaf extract (MLE 1:30) and the other treatments (soaking in wate; 24-epibrassinolide (EBL 10- 10, 10-8, and 10-6 M) and ascorbic acid (AsA 50, 100, and 150 mg.L-1)) were applied to moringa seeds and germination and growth were evaluated. To determine cold tolerance, moringa seedlings were cooled to temperatures of 20/15, 15/10 and 10/5 °C (day/night) for 7 and 14 days. Thereafter, the effects of stress duration and the recovery under optimal conditions were evaluated by means of morphological and physiological parameters of the seedlings. In addition, the ability of the species to tolerate negative temperatures was evaluated based on a freezing - thawing protocol and the capacity to acclimatize was tested. The genetic diversity in 25 accessions derived from 177 Moringa BAG genotypes was estimated using 20 ISSR markers. It was observed that the seed treatments favored moringa germination and seedling growth. Furthermore, the results of morphological and physiological parameters improved when seeds were treated with MLE 1:30. After eight days at 10/5 °C and four days of recovery under optimal conditions, the damages to the photosynthetic apparatus and cell membranes of moringa were found to be irreversible. The lethal freezing temperature that causes 50% injury to the moringa leaflets (LT50) was -2.8 °C, and no ability of the species to acclimatize could be observed. In the study on the genetic diversity of the Moringa BAG accessions, the 20 ISSR primers amplified 144 bands, of which 100% were polymorphic. The mean values of the expected heterozygous (He) and Shannon Index (I) were 0.11 and 0.12, respectively. STRUCTURE program analysis divided the genotypes into two groups. Finally, the results allowed the conclusion that the genetic diversity in the Moringa BAG is low.